2017
DOI: 10.1111/ecog.02424
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the importance of geographic replication and representativeness when estimating demographic rates, using a coastal species as a case study

Abstract: Demographic rates are rarely estimated over an entire species range, limiting empirical tests of ecological patterns and theories, and raising questions about the representativeness of studies that use data from a small part of a range. The uncertainty that results from using demographic rates from just a few sites is especially pervasive in population projections, which are critical for a wide range of questions in ecology and conservation. We developed a simple simulation to quantify how this lack of geograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 108 publications
0
18
0
Order By: Relevance
“…A male-biased offspring sex ratio would help to explain a male-biased adult sex ratio; however, we found neither a male-biased offspring sex ratio nor evidence for sex-specific nestling mortality that would lead to the observed differences in adult sex ratio. Further, studies have also found no sex differences in adult survival, with a mean survival rate of 0.44 for females and 0.49 for males (Field et al 2017).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A male-biased offspring sex ratio would help to explain a male-biased adult sex ratio; however, we found neither a male-biased offspring sex ratio nor evidence for sex-specific nestling mortality that would lead to the observed differences in adult sex ratio. Further, studies have also found no sex differences in adult survival, with a mean survival rate of 0.44 for females and 0.49 for males (Field et al 2017).…”
Section: Discussionmentioning
confidence: 97%
“…To further evaluate our findings of variation in offspring sex ratio in relation to adult sex ratio, we used capture data from a separate ongoing study utilizing systematic and targeted netting of adults from the same 5-yr study period to estimate the adult sex ratio in our 4 study sites (Field et al 2017). By including targeted netting of adult females on nests, our methods minimized the capture bias that typically favors males in systematic netting studies.…”
Section: Discussionmentioning
confidence: 99%
“…This plasticity, however, is likely insufficient in the face of sea‐level rise, which reduces high marsh habitat and modifies tidal regimes that disrupt synchronous breeding of sparrows with the 28‐day tidal cycle. The direct impacts of sea‐level rise are predicted to reduce the reproductive success of saltmarsh sparrows (Bayard & Elphick, ), which have already declined at a rate of 9% annually from 1998 to 2012 (Correll et al., ), leaving the species vulnerable to extinction within the next 50 years (Field et al., , ). The apparent adaptive capacity of saltmarsh sparrows, however, may enhance their ability to respond to management interventions targeted to mitigate nest flooding.…”
Section: Discussionmentioning
confidence: 99%
“…The raw pattern of bill measurements, uncorrected for body size, shows maximum bill surface areas near 42°N (near the southern boundary of the hybrid zone and the peak in regional sparrow density: Field et al 2018) and declines both to the south and north (Fig. Across all samples and sexes, bill surface area was 5.3 mm 2 larger for saltmarsh (mean ± 95% CI = 70.8 ± 0.8 mm 2 ) versus Nelson's (65.5 ± 0.9 mm 2 ) sparrows.…”
Section: Resultsmentioning
confidence: 99%
“…They do, however, still possess larger bills on average than their closest non-tidal-marsh relative (Shriver et al 2011, Greenlaw et al 2018, which is the convergent pattern across a large suite of coastal birds (Grenier andGreenberg 2005, Luther andGreenberg 2011). Importantly, however, saltmarsh sparrows also possess variation in breeding density independent of the temperature cline, as density is highest in the range center (Wiest et al 2016, Field et al 2018. Importantly, however, saltmarsh sparrows also possess variation in breeding density independent of the temperature cline, as density is highest in the range center (Wiest et al 2016, Field et al 2018.…”
Section: Introductionmentioning
confidence: 94%